Quantitative proteomics analysis of tomato root cell wall proteins in response to salt stress - Chen, Shuisen; Shi, Fei; Li, Cong; Sun, Quan; Ruan, Yanye (Frontiers in Plant Science, 2022)
Cell wall proteins perform diverse cellular functions in response to abiotic and biotic stresses. To elucidate the possible mechanisms of salt-stress tolerance in tomato. The 30 d seedlings of two tomatoes with contrasting salt tolerances were transplanted to salt stress (200 mM NaCl) for three days, and then, the cell wall proteins of seedling roots were analyzed by isobaric tags for relative and absolute quantification (iTRAQ). There were 82 and 81 cell wall proteins that changed significantly in the salt-tolerant tomato IL8-3 and the salt-sensitive tomato M82, respectively. The proteins associated with signal transduction and alterations to cell wall polysaccharides were increased in both IL8-3 and M82 cells wall in response to salt stress. In addition, many different or even opposite metabolic changes occurred between IL8-3 and M82 in response to salt stress. The salt-tolerant tomato IL8-3 experienced not only significantly decreased in Na+ accumulation but also an obviously enhanced in regulating redox balance and cell wall lignification in response to salt stress. Taken together, these results provide novel insight for further understanding the molecular mechanism of salt tolerance in tomato.